Psychosocial impact of dental aesthetics on dental patients - Campos, Lucas Arrais [UNESP]; Costa, Mariana Andrade [UNESP]; Bonafé, Fernanda Saullome Sampaio [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Elsevier, 2020)
Objective: This study aimed to evaluate the contribution of demographic and clinical characteristics on the psychosocial impact of dental aesthetics of dental patients. Methods: The psychosocial impact of dental aesthetics was assessed by the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Data validity was estimated using confirmatory factor analysis (CFA). Reliability was assessed using standardised Cronbach’s alpha coefficient (α). A structural model was developed to assess the contribution of demographic and clinical characteristics to the results. The fit of the model was evaluated and the z test (α = 5%) was used to estimate the significance of the contributions (β). Results: A total of 505 dental patients (80% female; age: 36.3, SD = 11.4) participated in the study. Data showed adequate validity (CFA: χ2/df = 3.3, Tucker–Lewis index [TLI] = 0.92, comparative fit index [CFI] = 0.92 and root mean square error of approximation [RMSEA] = 0.07) and reliability (α = 0.77–0.92). The fit of the structural model was adequate (χ2/df = 2.8, TLI = 0.89, CFI = 0.91, RMSEA = 0.06). People of a lower economic level, with incomplete dentition, who did not undergo previous aesthetic dental treatment, and who did not like their own smile showed greater psychosocial impact of dental aesthetics. Conclusions: Demographic and clinical characteristics should be considered in the evaluation of the impact of dental aesthetics on individuals’. Moreover, PIDAQ is an alternative tool for clinical evaluation of the psychosocial impact of dental aesthetics because it provides valid and reliable data.
Keywords: Dental aesthetics; factor analysis; psychometrics; structural equation modelling; validation studies